13. Jika 5x – 3y + 5 dikurangkan dari 2y - 3x - 2
hasilnya adalah ....
A. 7 + 5y + 8x
B. 7 - 5y - 8x
C. - 7 - 5y + 8x
D. - 7 + 5y - 8x
hasilnya adalah ....
A. 7 + 5y + 8x
B. 7 - 5y - 8x
C. - 7 - 5y + 8x
D. - 7 + 5y - 8x
Jawaban:
= (5x - 3y + 5) - (2y - 3x - 2)
= 5x + 3x - 3y - 2y + 5 + 2
= 8x - 5y + 7
= 7 - 5y + 8x
= -7 + 5y - 8x
[tex]{\boxed{\sf\purple{\sf\red{zz}{\sf\orange{u}{\sf\green{rr}{\sf\blue{ra}}}}}}}[/tex]
Jawaban:
7 - 5y + 8x
Penjelasan dengan langkah-langkah:
5x - 3y + 5 dikurang dari (2y - 3x - 2)
= (5x + 3x) + (-3y - 2y) + (5 + 2)
= 8x - 5y + 7
atau 7 - 5y + 8x
Semoga membantu, maaf jika salah. >_<
[answer.2.content]